Pengaruh Work From Home dan Lingkungan Kerja Terhadap Kinerja Selama Pandemi di PT. Jasaraharja Putera - Mudrikah; Sabeli Aliya (Permana : Jurnal Perpajakan, Manajemen, dan Akuntansi, 2022)
This study aims to determine how much influence work from home and work environment have on performance during the pandemic at PT. Jasaraharja Putera Palembang Branch. This type of research is quantitative research using multiple regression analysis techniques, classical assumption test, validity and reliability testing, hypothesis testing through t and f tests, and correlation coefficient analysis and determination. From the results of this study is the effect of work from home partially significant effect on the performance of PT. Jasaraharja Putera this can be seen from the T test, namely tcount of 2.487 > ttable of 2.026 with a significance of 0.018 <0.05, it can be concluded that partially there is a significant positive effect between work from home on performance. The influence of the work environment partially has no effect on the performance of PT. Jasaraharja Putera this can be seen from the T test, namely tcount of -0.645 < ttable of 0.026 with a significance level of 0.523 > 0.05. The work from home and work environment variables have a significant effect simultaneously (simultaneously) on the performance dependent variable with a value of fcount 9.612 > ftable 3.25 with a significance value of 0.00 < 0.05. Based on the coefficient of determination R Square (R) of 0.342 or 34.2%, it means that the contribution of the influence of work from home (X1) and the work environment (X2) to performance (Y) is 34.2% and the rest (100% - 34, 2%) 65.8% influenced by other factors not examined.